2022
DOI: 10.1016/j.celrep.2022.110295
|View full text |Cite
|
Sign up to set email alerts
|

Twist regulates Yorkie activity to guide lineage reprogramming of syncytial alary muscles

Abstract: Highlights d Twist mediates fate plasticity during transdifferentiation of syncytial muscle cells d Twist induces Yorkie activity to promote dedifferentiation and reprogramming d Twist/Yki/FGFR regulatory axis is required for lineage switch during reprogramming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…When we analyzed the YAP/TEAD-dependent transcripts, we confirmed that in the YAP-expressing cells, Zeb1 and Twist1 (referred as Twist), two key transcriptional repressors of E-cadherin and downstream targets of YAP/TEAD, were oppositely regulated in the LNCaP-YAP 1-WT and Y407F-expressing cells. However, E-cadherin (E-CAD) was strongly reduced in the YAP1-WT cells, and also in the Y40F mutant ( Figure 4 ) possibly through a more complex reciprocal regulation by Twist and YAP1 [ 23 , 24 ]. In fact, the reciprocally regulated Twist target gene N-cadherin (N-CAD) was suppressed only in the Y407F-expressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…When we analyzed the YAP/TEAD-dependent transcripts, we confirmed that in the YAP-expressing cells, Zeb1 and Twist1 (referred as Twist), two key transcriptional repressors of E-cadherin and downstream targets of YAP/TEAD, were oppositely regulated in the LNCaP-YAP 1-WT and Y407F-expressing cells. However, E-cadherin (E-CAD) was strongly reduced in the YAP1-WT cells, and also in the Y40F mutant ( Figure 4 ) possibly through a more complex reciprocal regulation by Twist and YAP1 [ 23 , 24 ]. In fact, the reciprocally regulated Twist target gene N-cadherin (N-CAD) was suppressed only in the Y407F-expressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, E-Cadherin was strongly reduced in the wt-YAP cells, and also in the Y40F mutant (Fig. 4) possibly through a more complex reciprocal regulation by Twist and YAP [23] [24]. And in fact, the reciprocally regulated Twist target gene N-Cadherin was suppressed only in the Y407F expressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Like AM FC specification, AM to VLM transdifferentiation is controlled by Org-1/Tbx1 and Tup/Islet1. It also requires Twi acting downstream of Org-1 ( Schaub et al, 2015 ; Rose et al, 2022 ). Further dissection of this naturally occurring transdifferentiation process will likely bring more information into mechanisms of cellular reprogramming during ontogeny and tissue regeneration.…”
Section: Trans-differentiation Of Ams At Metamorphosismentioning
confidence: 99%
“…More broadly, Tbx1 and Islet1 are major conserved actors in the genetic program controlling pharyngeal muscle development in chordates while Twi is involved in formation and regeneration of extraocular muscles ( Nathan et al, 2008 ; Sambasivan et al, 2011 ; Zhao et al, 2020 ; Whitman et al, 2022 ). In Drosophila, the Tbx1/Islet1 genetic hierarchy selectively controls AM/TARM development and, together with Twi, AM into VLM trans-differentiation ( Boukhatmi et al, 2014 ; Schaub et al, 2015 ; Rose et al, 2022 ). Whether the Tbx1/Islet1 hierarchy has been recruited during evolution for diversification and specific adaptations of striated muscles is an open question.…”
Section: Ancestral Origin and Evolution Of Ams; The Tbx1-islet1 (Twi)...mentioning
confidence: 99%